The threat of the ambrosia beetle Megaplatypus mutatus (Chapuis) (=Platypus mutatus Chapuis) to world poplar resources - Alfaro, René I. (2007)
We describe the life cycle of Megaplatypus mutatus (Chapuis) (=Platypus mutatus) and the damage it causes to poplar resources in Argentina. This insect, native to the subtropical and tropical areas of South America, has extended its range into temperate regions, reaching as far south as Neuquén in Argentinean Patagonia. The damage is caused by the adult insects, which bore large gallery systems into living poplars (Populus spp.), willows (Salix spp.) and many other broadleaf species, including important fruit trees species such as apples (Malus spp.), walnuts (Juglans spp.) and avocados (Persea spp.). The galleries degrade the lumber and weaken the tree stems, which often then break during windstorms. A recent introduction of M. mutatus to Italy demonstrates that this insect can be transported long distances between countries, and therefore presents a threat worldwide - particularly to poplar cultivation. We review the taxonomic nomenclature for this pest, provide a summary of the life cycle, hosts and damage and summarize actions taken to reduce the risk of introduction of M. mutatus to Canada.